Les dimensions du processus d’influence sociale et la supervision des stagiares en psychologie du counseling - Martin, France; Sabourin, Stéphane; Cyr, Mireille (Canadian Journal of Counselling and Psychotherapy, 1992)
Trainee's supervision is frequently conceptualized as a social influence process. The aim of the present literature review is to examine the dimensions underlying the social influence process in supervision, and to verity the empirical bases of unidimensional and multidimensional conceptions. Results of studies show the existence of more than one dimension. Yet, those various dimensions share some similarities on conceptual and empirical grounds. Moreover, discriminant validity of those dimensions is only partially demonstrated. A hierarchical conception is proposed, as well as suggestions of research.